ASSOCIATION OF β-ADRENORECEPTION SYSTEM GENE POLYMORPHISMS AND NON-TOXIC GOITER IN PATIENTS WITH HEART FAILURE* - S.M. Pyvovar; Yu.S. Rudyk; T.V. Lozyk; V.Yu. Galchinska; T.M. Bondar (Проблеми екології та медицини)
Predicting the course of heart failure (HF) is an urgent task of modern medical science. Given the increasing prevalence of the disease with age, it is necessary to take into account the presence of comorbid pathology. The aim of the research was to study the relationship between gene polymorphisms of the β-adrenoceptor system with non-toxic goiter (NTG) and the HF course. Materials and methods. The total of 285 patients with HF against the background of post-infarction cardiosclerosis were included into the study. Of these, 158 (55.42%) patients had a comorbidly unfavorable pathology - NTG. Genotyping of 4 polymorphisms (Gly389Arg of the β1-adrenoreceptor gene, Ser49Gly gene of the β1-adrenoceptor (β1-AP) gene, Gln27Glu of the β2-AP gene and Ser275 of the β3- G-protein subunit gene was performed usingpolymerase chain reaction (PCR). Genetic and epidemiological analysis was performed using the SNPStats software. The obtained results. The presence of the G-allele of the Ser49Gly polymorphism of the β1-AP gene is associated with an increase in the rate of NTG development (recessive heredity model, x2 = 3.719, p = 0.039). We found a tendency to the increase of NTG development rate (by 5.9%) in the presence of the allele C polymorphism of Ser275 gene GNβ3 (recessive model of heredity, x2 = 3,452, p = 0,068). The risk of "low triiodothyronine" syndrome development in patients with HF, running against the background of NTG increases in homozygotes (G / G) according to the polymorphism Ser49Gly (c, 145A> G) of the β1-AR gene (odds ratio (OR) = 9.19 (3.69-22.90), g = 0.044). In patients with HF, which runs against the background of NTG, with the presence of the G allele polymorphism Gln27Glu (c, 79C> G) of the β2-AP gene, the risk of reaching a combined endpoint within two years (OR = 3.05 (1.10-8.43) increases in a homozygous state and OR= 3.38 (1.47-7.82) in heterozygotes, at p = 0.008), the risk also increases with heterozygous (G / C) patients with the Gly389Arg (c, 1165G> C) polymorphism of the β1-AR gene in the presence of NTG (OR = 2.09 (1.00-4.37), p = 0.046). Conclusion. Congenital genetic differences in -adrenoceptor pathways may be associated with the development of non-toxic goiter and the long-term course of heart failure.